The Role of Innovative Organizational Culture and Digital Transformation Readiness in Educational Institution Performance - Zakiyyah, Dhiyauz; Abidin, Munirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Digital transformation in the world of education requires the readiness of institutions to respond to changes based on information technology. This study aims to analyze the influence of innovative organizational culture and digital transformation readiness on the performance of educational institutions. The method used is a quantitative approach with a correlational type through path analysis using the Partial Least Squares Structural Equation Modeling (PLS-SEM) model. The population of this study was 57 teachers and staff from SMKN 7 Malang who were used as the total sample. The data collection instrument in the form of a questionnaire, was analyzed through the SmartPLS application. The results of the study indicate that innovative organizational culture has a positive and significant effect on the performance of educational institutions (β = 0.812), as well as digital transformation readiness (β = 0.695). Furthermore, digital transformation readiness also has a significant effect on the performance of educational institutions (β = 0.291) and is able to be a mediating variable (indirect effect = 0.202). This study concludes that innovative organizational culture can improve the performance of educational institutions directly and through digital transformation readiness